Performance of Down syndrome subjects during a coincident timing task - Torriani-Pasin, Camila; Bonuzzi, Giordano M. G.; Soares, Marcos A.; Antunes, Gisele L.; Palma, Gisele C. S.; Monteiro, Carlos B. M.; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Perotti Junior, Alaércio; Wajnsztejn, Rubens; Corrêa, Umberto C (Springer Nature, 2013)
Background: The time synchronization is a very important ability for the acquisition and performance of motor skills that generate the need to adapt the actions of body segments to external events of the environment that are changing their position in space. Down Syndrome (DS) individuals may present some deficits to perform tasks with synchronization demand. We aimed to investigate the performance of individuals with DS in a simple Coincident Timing task. Method. 32 individuals were divided into 2 groups: the Down syndrome group (DSG) comprised of 16 individuals with average age of 20 (+/- 5 years old), and a control group (CG) comprised of 16 individuals of the same age. All individuals performed the Simple Timing (ST) task and their performance was measured in milliseconds. The study was conducted in a single phase with the execution of 20 consecutive trials for each participant. Results: There was a significant difference in the intergroup analysis for the accuracy adjustment - Absolute Error (Z = 3.656, p = 0.001); and for the performance consistence - Variable Error (Z = 2.939, p = 0.003). Conclusion: DS individuals have more difficulty in integrating the motor action to an external stimulus and they also present more inconsistence in performance. Both groups presented the same tendency to delay their motor responses. © 2013 Torriani-Pasin et al.; licensee BioMed Central Ltd.
Keywords: Down syndrome; Growth & development; Motor activity; Task performance and analysis; absolute error; accuracy; adult; chronology; clinical article; coincident timing task; controlled study; error; executive function; human; mental performance; motor activity; simple timing task; task performance; time series analysis